Analysis of Institutional Ownership, Managerial Ownership, Profitability, Company Growth, Asset Structure Versus Debt Policy on Real Estate and Building Construction on the Indonesia Stock Exchange 2016-2019 - Denny Chandra; Leonardi, Dewi Anggriani Wijaya; Jholant Bringg Luck Amelia Br Sinaga (Journal of Research in Business, Economics, and Education, 2021)
This research is a study to determine the analysis of institutional ownership, managerial ownership, profitability, company growth, asset structure on debt policy. The population used is all real estate and building construction companies listed on the Indonesia Stock Exchange. The sample was selected by purposive sampling technique. This study uses secondary data and is tested using the analytical method used is multiple linear regression, the coefficient of determination is tested simultaneously (F-Test) and partially (T-Test). The results of the regression analysis show that the effect of the independent variables (institutional ownership, managerial ownership, profitability, company growth, asset structure) in explaining the dependent variable (debt policy) is 52.6%. The results show that profitability and asset structure partially affect debt policy, while institutional ownership, managerial ownership, and asset structure partially do not affect debt policy. The results show that institutional ownership, managerial ownership, profitability, company growth, asset structure simultaneously affect debt policy.